PENINGKATAN KOMPETENSI GURU MELALUI SUPERVISI BERKELANJUTAN MASA PANDEMI COVID 19 DI SEKOLAH DASAR NEGERI 3 WAKAN KECAMATAN JEROWARU SEMESTER GANJIL TAHUN PELAJARAN 2021/2022 - Muttaqin, Zaenal (LPPM Institut Pendidikan Nusantara Global, 2023)
The research conducted was school action research (SAR) which raises questions about how teachers can use existing learning media in the learning process in the classroom with the intention of increasing the quality of learning conducted in class and the evaluation was carried out through supervising activities of the principal in class when learning. This school action research activity was carried out at SDN 3 Wakan for 3 months, from October to December 2021 by going through cycle stages. The purpose of this school action research (SAR) is to find out to what extent the supervision carried out by the school principal followed by the provision of guidance/treatment of target teachers can improve the teacher's ability to apply learning models in class. This school action research (SAR) was carried out in 2 cycles, the results of the actions taken proved to be able to improve teacher abilities by achieving ideal standards. In the first cycle of improving the ability of teachers after conducting class supervision after coaching on the use of new learning media reached around 33.33% in cycle II it could increase to 100%. The average score obtained after class supervision in cycle I was 63.30 and increased in cycle II to 83.33, meaning that there was an increase of 20.03 and the level of completeness as a group/classical in cycle I reached 33.33% and in cycle II increased to 100%. The results of this school action research show that school principal coaching can improve teachers' ability to use instructional media in the learning process.